Christelike onderwys in die praktyk: ’n Evaluering van die huidige stand van sake - Walt, J. L. van der (Koers, 1990)
Despite many years of reflection on and discussion of the theory and practice of Christian education in the RSA and other parts of the Western world, full justice has so far not been done to the ideals of Christian education in the practical situation of the classroom. This conclusion is drawn on the basis of an analysis of certain utterances by educationalists from four different parts of the world as well as on an analysis of some books generally used in RSA schools. The article is concluded with some suggestions towards rectifying the matter.